1998
DOI: 10.1111/j.1151-2916.1998.tb02715.x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characterization of Superplastic SiO2‐doped TZP with a Small Amount of Oxide Addition

Abstract: The microstructures of 5 wt% SiO2‐doped TZP, 5 wt% (SiO2+ 2 wt% MgO)‐doped TZP, and 5 wt% (SiO2+ 2 wt% Al2O3)‐doped TZP are characterized by high‐resolution electron microscopy, energy‐dispersive X‐ray spectroscopy, and electron energy loss spectroscopy. An amorphous phase is formed at multiple grain junctions but not along the grain‐boundary faces in these three materials. A small addition of MgO and Al2O3 into the SiO2 phase results in a marked reduction in tensile ductility of SiO2‐doped TZP. This reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 16 publications
1
19
0
2
Order By: Relevance
“…It has been reported that dopant cations are likely to segregate at grain boundaries in TZP. 10,11,27,28) The dependence of groove angle on dopant is supposed to result from segregation of dopant at grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that dopant cations are likely to segregate at grain boundaries in TZP. 10,11,27,28) The dependence of groove angle on dopant is supposed to result from segregation of dopant at grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned before, dopants are likely to segregate to grain boundaries in TZP. 10,11,27,28) The segregated dopant probably changes the covalent bonding state nearby grain boundaries. Effective covalency can be evaluated using total BOP of all bonds in a cluster.…”
Section: Chemical Bonding State Of Doped Tzpmentioning
confidence: 99%
See 1 more Smart Citation
“…Basándose en resultados conocidos de la teoría de fluidos, estos autores derivan la siguiente ecuación de fluencia en tracción (15): [6] donde Q es una energía de activación efectiva y α un parámetro ajustable. De este modo se justifica la variación exponencial de la velocidad de deformación con la tensión aplicada, en buen acuerdo con buena parte de las observaciones experimentales.…”
Section: Fluencia Por Cavitaciónunclassified
“…La fase secundaria se localiza fundamentalmente en "bolsas" situadas en puntos de contacto entre varios granos (5)(6)(7). Además, una fracción de la fase secundaria vítrea se localiza también en las fronteras de grano, formando una película intergranular delgada (de entre 0.5 y 2 nm de espesor), capaz de soportar tensiones normales (8).…”
Section: Introductionunclassified